THE EFFECTIVENESS OF USING ENGLISH LABORATORY IN LISTENING - Rahmatun Nisa (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2017)
Listening is one of English skills that should be achieved by students; it is following and understandingthe sound and it is hearing with a purpose and requires concentration. Thus, this paper aimed to find out to know which one is effective either usinglaboratory or tape recorder in listening and to find out the different results of listening tests by using laboratory than that of by using tape recorder.The research was conducted at LDC UIN Ar-raniry Banda Aceh, and the sample was the students of EnglishDepartment of UIN Ar-raniry. The numbers of sample were 27 students. The method used in this research was descriptive quantitative, and the test and interview were used as the instruments in order to see the ability of English Department Students.After analyzing the data the result of both tests was different. The result test by using tape recorder was: Â while the result test by using laboratory was: . Then from the interview, it was found that most of the studentssaid that they felt more comfort and easier study listening in the laboratory than that by using tape recorder in the class room.It can be inferred that listening by using laboratory is more effective than using tape recorder in class room.